Online reservation system development and digital payment integration in car wash business: Case study of car wash sniper - Purwaningsih, Ratna; Murti, Alif Catur; Nindyasari, Ratih (SHM Publisher, 2025)
This study aims to develop a website-based online reservation system at Car Wash Sniper with digital payment integration to improve operational efficiency and customer convenience. The system design method uses a waterfall model approach that includes needs analysis, system design, implementation, testing, and maintenance. Black box testing is also carried out to test the suitability of the system with the design that has been developed. To support the payment process, this system is integrated with Midtrans as a payment gateway that provides various payment options such as bank transfers, e-wallets, and credit cards safely and in real-time. The results of the study show that this system is able to optimize the reservation process, reduce queues, and increase customer satisfaction. The novelty of this research by developing a system that is integrated with digital payments, making transactions more practical, efficient, and transparent. This system can be an innovative solution for business actors in the car wash industry to improve efficiency and service quality.